Solve for x : 9x + 2 - 6.3x + 1 + 1 = 0

0 votes
1 view
asked Feb 9 in Class X Maths by muskan15 (-3,244 points)

Solve for  x : 9x + 2  - 6.3x + 1  + 1 = 0

Please log in or register to answer this question.

1 Answer

0 votes
answered Feb 9 by navnit40 (-4,331 points)

Given equation  9x + 2  - 6.3x + 1  + 1 = 0

⇒ 9x.92 – 6.3x.31 + 1 = 0

⇒ 81.(32)x  - 18.3x + 1 = 0

⇒ 81.32x – 18.3x + 1 = 0

Putting  3x = y, then it becomes 81y2 – 18y + 1 = 0

⇒ 81y2 – 9y – 9y + 1 = 0

⇒ 9y(9y – 1) – 1(9y – 1) = 0

⇒  (9y- 1)(9y – 1) = 0

⇒ 9y = 1 ⇒ y = 1/9

But 3x = 1/9 = 1/32 = 3-2

∴   x = - 2

Hence, the required root is – 2.

Related questions